Phân loại nghĩa tình thái của câu tiếng việt /Nguyễn Thị Nhung. - Nguyễn, Thị Nhung.
This paper discusses the categorization of modality of sentence in Vietnamese.I first offer a genegal categorization of meaning of modality in previous researches.Based on that, the paper offer a set of criteria to categorize modaliti in Vietnamese sentences.The criteria are subjectivity, the subject in relation with the speaker,type of relationship between the speaker and individual subject, the criteria to categorize characteristics of modality: functionality and obligation, realism and non-realism, positivity, negativity or neutrlity, quantity and quality. The results are demonstrted in group, sub-groups, typology and characteristics according to their meaning s.Finally, I offer descriptionss of the characteristics of espistemic modality, evaluate modality, emotion modality, moral modality and attitude modality in Vietnamese sentences.